0581 The Impact of REM-AHI on Revascularized Cardiac Patients. (12th April 2019) - Newitt, Jennifer; Strollo, Patrick J; Balcan, Baran; Thunstrom, Erik; Peker, Yuksel
Abstract: Introduction: Rapid-eye movement (REM) sleep compared to non-REM sleep is associated with increases in sympathetic activity and greater oxygen desaturations believed to increase cardiovascular risk in patients with obstructive sleep apnea (OSA). Previous studies have demonstrated REM predominant OSA to be longitudinally associated with hypertension. We examined the differential impact of REM-predominant-OSA compared to non-REM-predominant-OSA on cardiovascular function in participants in the RICCADSA cohort with revascularized coronary artery disease (CAD) and OSA at baseline. Methods: TheR andomizedI ntervention with continuous positive airway pressure (C PAP) inCAD and OSA (RICCADSA) trial randomized CAD non-sleepy participants with OSA (n= 244) to CPAP (n=122) or no CPAP (n=122). Baseline polysomnography (PSG) was scored by "Chicago Criteria" defining obstructive apnea as a complete airflow cessation or hypopnea as a 50% reduction in airflow or a clear reduction in airflow accompanied by arousal from sleep or a 4% oxygen desaturation. Baseline cardiac function was assessed by echocardiography and pro-BNP. Two-sample t-test analysis was performed to evaluate REM-AHI, overall-AHI, percent time oxygen saturation below 90% in patients with REM-predominant-OSA on PSG compared to non-REM-predominant-OSA. REM-predominant-OSA was defined as at least 240 minutes total sleep time plus at least 30 minutes REM sleep time plus REM/NREM-AHI ratio greater than 2. Results: REM-predominant-OSA participants (n=70) compared to non-REM-predominant-OSA participants (n=209) were similar in terms of age (p-value 0.3), SBP (p-value 0.58), current smoking status (p-value 0.95), treated hypertension (p-value 0.42), Epworth Sleepiness Scale (p-value 0.39). The REM-predominant-OSA group had significantly less males (p-value <0.001) and greater BMI (p-value 0.02). The REM-predominant-OSA group had significantly greater REM-AHI (55.1 +/- 21.8 events/hr) compared to non-REM-predominant-OSA group (38.0 +/- 23.5) with p-value <0.001. Conclusion: REM-AHI was significantly greater in participants with REM-predominant-OSA compared to those with non-REM-predominant-OSA at baseline. Utilizing "Chicago Criteria" for scoring AHI, REM predominant OSA was not associated with impaired cardiovascular function at baseline. Support (If Any): Funding provided by Swedish Research Council (521-2011-537 and 521-2013-3439); the Swedish Heart-Lung Foundation (20080592, 20090708 and 20100664); NIH T32 HL082610-11; ATS ASPIRE fellowship.